2017
DOI: 10.1002/iub.1609
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CD133 and ezrin expression in colorectal carcinoma

Abstract: Despite the improvement in the diagnostic and the therapeutic modalities, colorectal cancer (CRC) morbidity and mortality remain high in both the developed and the developing countries. So, we are in a need to recognize new efficient diagnostic and prognostic biomarkers of CRC. That may help in providing individualized targeted therapy for this lethal malignancy. In this study, we investigated the expression and the prognostic significance of CD133 and ezrin mRNA and protein by quantitative RT-PCR and immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
9
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
6
9
4
Order By: Relevance
“…In the current study, there was no significant relation between ezrin expression and histopathological type, gender and tumor site. Similar results were obtained by Patara et al, (2011); Jin et al, ( 2012) and Fathi et al, (2017).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the current study, there was no significant relation between ezrin expression and histopathological type, gender and tumor site. Similar results were obtained by Patara et al, (2011); Jin et al, ( 2012) and Fathi et al, (2017).…”
Section: Discussionsupporting
confidence: 89%
“…Similar result was obtained by Wang et al, (2009) and Patara et al, (2011). Against this finding, Lin and Chen, (2013) and Fathi et al, (2017) reported that no significant relationship was found between ezrin expression and degree of differentiation of colorectal carcinoma in their studied cases. This may be attributed to different sample size.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In cancer progression, ezrin is involved in cell adhesion, migration, and invasion as well as tumor growth and metastasis by acting as a key molecule involved in membrane organization or cellular signal transduction [9][10][11][12]. Due to the potential importance of ezrin in cancer, the prognostic significance of ezrin has been evaluated in numerous types of cancers [13][14][15][16]. However, the results have been somewhat contradictory [15,17,18].…”
mentioning
confidence: 99%